Bleeding profile satisfaction and pain and ease of placement with levonorgestrel 19.5 mg IUD: findings from the Kyleena® Satisfaction study. (2nd January 2023) - Donders, Gilbert; Kopp Kallner, Helena; Hauck, Brian; Bauerfeind, Anja; Frenz, Ann-Kathrin; Zvolanek, Michal; Stovall, Dale W.
Abstract: Purpose: To investigate bleeding profile satisfaction and pain and ease of placement with levonorgestrel 19.5 mg IUD in routine clinical practice. Methods: Women who independently chose levonorgestrel 19.5 mg IUD during routine counselling were invited to participate in this prospective, multinational, observational study. Patient-reported pain and clinician-reported ease of placement were assessed. Bleeding profile satisfaction was evaluated at 12 months/premature end of observation. Results: Most participants (77.8%, n = 878/1129) rated levonorgestrel 19.5 mg IUD placement pain as 'none' or 'mild' and most clinicians (91.1%, n = 1029/1129) rated placement as 'easy'. Pain was more often rated higher in nulliparous compared with parous ( p < .0001) and younger (<26 years) compared with older participants ( p < .0001), although 67.7% and 69.0% of nulliparous and younger participants respectively reported 'none' or 'mild' pain. Bleeding profile satisfaction at 12 months/end of observation was similar in parous (72.9%, n = 318/436) and nulliparous (69.6%, n = 314/451) participants. Most participants irrespective of age reported bleeding profile satisfaction, ranging from 67.8% ( n = 206/304) for 18–25 years to 76.5% ( n = 218/285) for >35 years. Conclusion: We observed high bleeding profile satisfaction regardless of age or parity with levonorgestrel 19.5 mg IUD and confirmed that device placement is easy and associated with no more than mild pain in most cases in routine clinical practice. Real-world evidence from the Kyleena ® Satisfaction Study in routine clinical practice shows high bleeding profile satisfaction with levonorgestrel 19.5 mg IUD regardless of age or parity. IUD placement was easy and associated with little to no pain for most women.